2020
DOI: 10.21203/rs.3.rs-119477/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Salmon gut microbiota correlates with disease infection status: potential for monitoring health in farmed animals

Abstract: Background Infectious diseases cause significant production losses in aquaculture every year. Since the gut microbiota plays an essential role in regulating the host immune system, health and physiology, altered gut microbiota compositions are often associated with a diseased status. However, few studies have examined the association between disease severity and degree of gut dysbiosis, especially when the gut is not the site of the primary infection. Moreover, there is a lack of knowledge on whether bath tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…As the Atlantic salmon progressed towards the adult stage, the enrichment of genus Mycoplasma at SW2 and SW3 time points compared to FW and SW1 was one of the most prominent differences found in our study, possibly indicating that the host is a determinant for microbial assemblage by attracting specific bacterial communities depending on the developmental stage of the fish [ 53 , 54 ]. Previous studies have found Mycoplasma , a member of the core microbiota, to be one of the most abundant bacteria in farmed as well as wild Atlantic salmon during seawater stages [ 26 , 55 59 ] reaching levels above 70% of total abundance in certain cases [ 19 , 45 , 58 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As the Atlantic salmon progressed towards the adult stage, the enrichment of genus Mycoplasma at SW2 and SW3 time points compared to FW and SW1 was one of the most prominent differences found in our study, possibly indicating that the host is a determinant for microbial assemblage by attracting specific bacterial communities depending on the developmental stage of the fish [ 53 , 54 ]. Previous studies have found Mycoplasma , a member of the core microbiota, to be one of the most abundant bacteria in farmed as well as wild Atlantic salmon during seawater stages [ 26 , 55 59 ] reaching levels above 70% of total abundance in certain cases [ 19 , 45 , 58 ].…”
Section: Discussionmentioning
confidence: 96%
“…For example, Mycoplasma abundance was strongly associated with flesh color darkness, suggesting a role in the production of carotenoids [ 60 ]. Moreover, the Mycoplasma has shown ecological and functional associations with the host [ 61 ] and is positively correlated with body weight [ 54 ]. However, the present study did not show a significant association between the relative abundance of Mycoplasma and the observed host responses.…”
Section: Discussionmentioning
confidence: 99%
“…The fish gut microbiome is essential to systemic function, fish health 37 , immune support 38 and digestive capacity 39 . However, the factors that govern the microbial community colonisation, assembly, and succession in fish species are poorly understood, in terms of both the ecological assembly mechanisms and development within the life cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, uorescent in situ hybridization suggested that salmonid strains of Mycoplasma are intracellular [52]. The absence of pathogenicity genes in the salmonid strains [51] suggests a mutually bene cial relationship, as observed in the hadal sail sh, where the Mycoplasma is bene cial to the host by providing biotin in a nutrient-poor environment [53] and aiding in host defence [53,54]. In the present study, we observed 2 OTUs belonging to the genus Mycoplasma and they were differentially abundant in all feeding groups (except the inulin2 group).…”
Section: Discussionmentioning
confidence: 99%